2012
DOI: 10.1002/mus.23441
|View full text |Cite
|
Sign up to set email alerts
|

Normokalemic periodic paralysis is not a distinct disease

Abstract: Our findings support the notion that normoKPP is not a distinct disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 11 publications
1
8
0
Order By: Relevance
“…In addition, more and more findings supported the notion that normoKPP was not a distinct disease and normokalemia could occur during attacks in patients with hyperPP. 9 However, low blood potassium level was observed in our patient who carries a mutation at codon 675 of the gene SCN4A. The patient exhibited the characteristic clinical and laboratory features of hypoPP, including hypokalemia during attacks and effective remission of weakness after supplying potassium.…”
Section: Dicussionmentioning
confidence: 53%
See 2 more Smart Citations
“…In addition, more and more findings supported the notion that normoKPP was not a distinct disease and normokalemia could occur during attacks in patients with hyperPP. 9 However, low blood potassium level was observed in our patient who carries a mutation at codon 675 of the gene SCN4A. The patient exhibited the characteristic clinical and laboratory features of hypoPP, including hypokalemia during attacks and effective remission of weakness after supplying potassium.…”
Section: Dicussionmentioning
confidence: 53%
“…Recently, a number of studies [7][8][9] have revealed that mutation R675Q in SCN4A mainly caused 2 kinds of disease: hyperPP and normoKPP (normokalemic periodic paralysis). In addition, more and more findings supported the notion that normoKPP was not a distinct disease and normokalemia could occur during attacks in patients with hyperPP.…”
Section: Dicussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The symptoms usually last for minutes to hours and are triggered by fasting, ingestion of potassium-containing foods, or vigorous exercise. Transient normokalemia, or even hypokalemia, can be measured during attacks, thus making the disease occasionally challenging to diagnose8). Gain-of-function mutations in the skeletal muscle voltage-gated sodium channel gene, SCN4A , impair channel inactivation and cause a persistent inward sodium current, which leads to increased membrane excitability and myotonia or reduced excitability with flaccid paralysis depending on the degree of membrane depolarization.…”
Section: Channelopathies In the Nervous Systemmentioning
confidence: 99%
“…Mutation screening was performed by sequencing the entire coding region of the CACNA1S, SCN4A, and KCNJ2 genes, as described elsewhere15,16). The clinical details of some patients have been reported previously2,16,17,18). Of these, we selected the three who presented with the most obvious symptoms of HOKPP in terms of both severity and frequency of paralytic attacks.…”
Section: Methodsmentioning
confidence: 99%